Smoking and Its Impacts on Absenteeism and Stress: A Preliminary Study - Jong, Jee Leong; Helmi, Sumilan; Heng, Chin Siong; Florianna, Lendai Michael (UNIMAS Publisher, 2016)
The article highlights a preliminary study on smoking and its impact on absenteeism and stress in the work place. The article also includes an application of the Theory of Planned Behaviour in explaining the behavior of smoking. The Theory of Planned Behavior which was proposed by Icek Ajzen is used to predict an individual’s behav-ioural control and intention which are influenced by attitude and social norms to per-form a behaviour. This article also discusses previous researches done on smoking and its relationship with absenteeism and stress among employees in organizations.